Adaptive Personality, Communication Patterns and Psychological Health: A Cross-cultural Adaptation Study of Korean Expatriates in Indonesia - Yang Soo Kim; Young Hun Koh (Intercultural Communication Studies, 2026)
Adaptive Personality, Communication Patterns and Psychological Health: A Cross-cultural Adaptation Study of Korean Expatriates in Indonesia